Association between HIV PrEP indications and use in a national sexual network study of US men who have sex with men. Issue 10 (3rd October 2021) - Weiss, Kevin M.; Prasad, Pragati; Sanchez, Travis; Goodreau, Steven M.; Jenness, Samuel M.
Abstract: Introduction: HIV pre‐exposure prophylaxis (PrEP) is effective in preventing HIV transmission. United States Public Health Service (USPHS) clinical practice guidelines define biobehavioral indications for initiation. To assess guideline implementation, it is critical to quantify PrEP nonusers who are indicated and PrEP users who are not indicated. We sought to estimate current PrEP use among US men who have sex with men (MSM), characterize whether their PrEP use aligned with their current indications for PrEP, and assess whether the association between PrEP indications and PrEP use differed by demography or geography. Methods: Using data from a US web‐based sexual network study of MSM between 2017 and 2019, we measured PrEP usage and assessed whether respondents met indications for PrEP. Log‐binomial regression was used to estimate the relationship between PrEP indications and PrEP use, with adjustment for geography, age and race/ethnicity. Results: Of 3508 sexually active, HIV‐negative MSM, 34% met indications for PrEP. The proportion with current PrEP use was 32% among MSM meeting indications and 11% among those without indications. Nearly 40% of those currently using PrEP did not meet indications for PrEP, and 68% of MSM with indications for PrEP were not currently using PrEP. After adjusting for geography and demographics, MSM with PrEP indications were about three times as likely to be currently using PrEP. This association varied slightly, but not significantly, by geographic region, age and race/ethnicity. Conclusions: Indications for PrEP strongly predicted current PrEP use among US MSM. However, we identified substantial misalignment between indications and use in both directions (indicated MSM who were not benefitting from PrEP, and MSM taking PrEP while not presently being indicated). PrEP underuse by those at greatest risk for HIV acquisition may limit the projected impact of PrEP implementation, despite reported increases in PrEP provision. This calls for further implementation efforts to improve PrEP delivery to those most in need during periods of elevated sexual risk and to close the gap between indications and uptake.